Algorithmic Fairness in AI - Pfeiffer, Jella; Gutschow, Julia; Haas, Christian; Möslein, Florian; Maspfuhl, Oliver; Borgers, Frederik; Alpsancar, Suzana (Business & Information Systems Engineering)
Keywords: Information Systems

Faktor Mensch. Jahrbuch Technikphilosophie 2023
With the focus topic “The Human Factor”, the Jahrbuch Technikphilosophie 2023 aims to investigate on the one hand the manifold arrangements of the deficiency in the technical field (and especially “new” technologies): How do machine worlds, user interfaces, implementation strategies, or even entire large-scale technological ecosystems model, compensate, and even parody “the” human being – that is, “their” version of ourselves? How does technology discriminate? How does it educate? To what extent can it “reduce” the human? On the other hand, it is necessary to take a new look at what “human” actually means in precisely this context, and to reexamine anthropology as part of theories of technology and discourses on technology. Criticism of technology must therefore also be criticism of man. With contributions by Fabian Anicker, Petra Gehring, Axel Gelfert, Martina Heßler, Andreas Kaminski, Ruth Karl, Katerina Krtilova, Joachim Landkammer, Kevin Liggieri, Felix Maschewski, Nicola Mößner, Anna-Verena Nosthoff, Felix Reda, Jean Paul Sartre, Björn Schembera, Stefan Schöberlein, Marcel Siegler, Florian Sprenger and Martin Warnke.

What is AI Ethics? Ethics as means of self-regulation and the need for critical reflection - Alpsancar, Suzana (International Conference on Computer Ethics 2023)

TA und Zeitdiagnosen. TA als Zeitdiagnose? - Alpsancar, Suzana (Technikfolgenabschätzung. Handbuch für Wissenschaft und Praxis)

„Vom Fahr-Zeug zum Fahr-Ding. Ein Heideggerianischer Kommentar zum autonomen Automobil“ - Alpsancar, Suzana (Autonome Autos – Die Zukunft des Verkehrs und die Dispositive der Mobilität)

Organprojektion - Alpsancar, Suzana (Mensch-Maschine-Interaktion: Handbuch zu Geschichte – Kultur – Ethik)

Computation - Alpsancar, Suzana (Mensch-Maschine-Interaktion: Handbuch zu Geschichte – Kultur – Ethik)

Arbeit und Technik? Zur Anschlussfähigkeit des Arbeitsparadigmas am Beispiel Ernst Kapp - Alpsancar, Suzana (Ernst Kapp und die Anthropologie der Medien)

Wer handelt mit unsichtbaren Schnittstellen? - Alpsancar, Suzana (Unterwachen und Schlafen. Anthropophile Medien nach dem Interface)

Die Ethik der Künstlichen Intelligenz - Alpsancar, Suzana (BTU News - September 2018)